Land Use Change in Buffer Zone of Chitwan National Park, Nepal between 1978 and 1999 - Baidya, N. G.; Bhuju, D. R.; Kandel, P. (Ecoprint: An International Journal of Ecology, 2010)
Land use dynamics in the Buffer Zone of Chitwan National Park was assessed by integrated use of Remote Sensing and Geographic Information System covering 1978, 1992 and 1999. Among all land-use type, forest was the most dominating land-use in 1978 covering 45.33% of total study area. However, the agricultural land became the most dominating land-use since 1992. The study found that since 1978 to 1999 there was increase in agricultural land by 67.28 km2, built-up area by 0.81 km2 and shrub-land by 7.68 km2. Whereas, the forest decreased by 62.23 km2, grassland by 11.38 km2 and water bodies by 2.16 km2. Vegetation density analysis using Normalized Difference Vegetation Index (NDVI) revealed that the densely vegetated area decreased by 5.03 km2 in a time-span of less than 10 years. Despite the successful community forest management in the BZ of CNP, this study showed a decline in densely forested area. Key words: GIS, Land use types, management, Remote sensing, Vegetation. DOI: 10.3126/eco.v16i0.3478 ECOPRINT 16: 79-86, 2009